The chosen we : Black women's empowerment in higher education - Winkle-Wagner, Rachelle; Slaughter-Defoe, Diana T. (Albany, NY : State University of New York Press, 2023)
Draws on and centers oral histories with Black women college graduates to demonstrate the role of community in fostering their success in and beyond education.
Introduction to the foreword author, Dr. Diana Slaughter -- Foreword -- Acknowledgments -- Part I. Black women's self-determination in education from here to eternity -- Chapter 1. The collective history of Black women's ways of knowing -- Chapter 2. From the unchosen me to the chosen we : Black women elevating Black women -- Part II. From individualism to transformative community at predominantly White institutions (PWIs) -- Chapter 3. Creating an oasis out of isolation : relationships that provide solace on White campuses -- Chapter 4. Unapologetically embracing Blackness : the importance of Black student organizations on predominantly White campuses -- Part III. From a collective legacy of racial uplift to empowered individual identity at historically Black colleges and universities (HBCUs) -- Chapter 5. Blackness-as-greatness : the normalization of nuanced views of Black excellence within HBCUs -- Chapter 6. HBCUs as home and family : embracing intersectional and nuanced Blackness through inclusion -- Part IV. Embodying race, institutional memory, and the Chosen We -- Chapter 7. From "unity" to "isolation" : comparing experiences within HBCUs and PWIs -- Chapter 8. In sickness and health on campus : the health inferences of college contexts and health in 60 years of oral history -- Appendix A. Putting Black women at the center as a White woman : an oral history methodology -- Appendix B. Participants quoted in the book -- Appendix C. Reading list of other publications from the project -- Notes -- References -- Index.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (ProQuest Ebook Central, viewed February 15, 2024).
JSTOR
Keywords: African American women -- Education (Higher); African American women college students -- Social conditions; African American college graduates -- Interviews; African American women -- Interviews; Universities and colleges -- United States -- Sociological aspects; Education, Higher; Electronic books; Étudiantes noires américaines -- Conditions sociales; Diplômés d'université noirs américains -- Entretiens; Noires américaines -- Entretiens; Universités -- États-Unis -- Aspect sociologique; Enseignement supérieur.; Livres numériques.; higher education; e-books.; EDUCATION / Higher; African American college graduates; African American women; African American women -- Education (Higher); Universities and colleges -- Sociological aspects; United States; Electronic books; Interviews